ABC - Good Morning America / ABC 7 – Eyewitness News / WABC-TV - Live! With Regis & Kelly
The tape contains two episodes of ABC’s “Good Morning America” with Charles Gibson, Robin Roberts, and Diane Sawyer, segments of ABC 7 Eyewitness News with Lori Stokes, and an incomplete episode of Live! With Regis & Kelly. The programs include: Dan Harris’s report from Baghdad, Iraq on U.S. diplomacy and the possible war on Iraq; Claire Shipman’s report from Istanbul, Turkey on the negotiations between the U.S. and Turkey to obtain passage for the U.S. troops to reach Northern Iraq; interview with a 4th grade teacher who has been summoned to active duty and is leaving for war; correspondent Taina Hernandez’s interview with Samantha Geimer, the woman who sued filmmaker Roman Polanski in 1988 alleging sexual assault; Robin Robertson’s report on the White House’s call to gain support for waging a war in Iraq; weather forecast; traffic news; movie reviews.